Toxicity of copper intake: lipid profile, oxidative stress and susceptibility to renal dysfunction - Galhardi, C. M.; Diniz, Y. S.; Faine, L. A.; Rodrigues, H. G.; Burneiko, RCM; Ribas, B. O.; Novelli, ELB (Elsevier B.V., 2004)
The present study was carried out to investigate the effects of copper (Cu) intake on lipid profile, oxidative stress and tissue damage in normal and in diabetic condition. Since diabetes mellitus is a situation of high-risk susceptibility to toxic compounds, we examined potential early markers of Cu excess in diabetic animals. Male Wistar rats, at 60-days-old were divided into six groups of eight rats each. The control(C) received saline from gastric tube, the no-diabetic(Cu-10), treated with 10 mg/kg of Cu(Cu(++)-CuSO(4), gastric tube), no-diabetic with Cu-60mg/kg(Cu-60), diabetic(D), diabetic low-Cu(DCu-10) and diabetic high-Cu(DCu-60). Diabetes was induced by an ip injection of streptozotocin (60mg/kg). After 30 days of treatments, no changes we're observed in serum lactate dehydrogenase, alanine transaminase and alkaline phosphatase; indicating no adverse effects on cardiac and hepatic tissues. D-rats had glucose intolerance and dyslipidemic profile. Cholesterol and LDL-cholesterol were higher in Cu-60 and DCu-60 than in C, Cu-10 and D and DCu-10 groups respectively. Cu-60 rats had higher lipid hydroperoxide (HP) and lower superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) serum activities than C and Cu-10 rats. LH was increased and GSH-Px was decreased, while no alterations were observed in SOD and catalase in serum of DCu-60 animals. DCu-60 rats had increased urinary glucose, creatinine and albumin. In conclusion, Cu intake at high concentration induced adverse effects on lipid profile, associated with oxidative stress and diminished activities of antioxidant enzymes. Diabetic animals were more susceptible to copper toxicity. High Cu intake induced dyslipidemic profile, oxidative stress and kidney dysfunction in diabetic condition. Copper renal toxicity was associated with oxidative stress and reduction at least, one of the antioxidant enzymes. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: copper; lipid profile; oxidative stress; kidney; Diabetes mellitus